Gambaran Pola Asuh Nenek pada Anak Broken Home di Kota Banjarmasin - Hayatunisa, Hayatunisa; Abidin, Muhammad Zainal; Hairina, Yulia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2023)
Parents an important role in helping the process of nurturing or educating children. ideally parenting is carried out by parents for their children, in certain cases, care is also carried out by grandmothers. This can happen due to several cases, one of which is a broken home. This study to determine the description of grandmother’s parenting and its inhibiting factors. This study uses a qualitative with a qualitative descriptive methode. The subject there are 3 grandmothers. Research location in the city of Banjarmasin. Data collection by interview and observation. Subject selection used purposive sampling technique, namely the subject was predetermined criteria. The results of the study that the parenting style three subjects tended to be permissive, the way for the three subjects was by giving examples and advice. While the inhibiting factors in this study are economic and environmental. The results of this study material in the field of education. Keywords: Broken Home; Grandma’s Parenting